Osteochondral autograft in the treatment of osteochondral lesions of the talus: a report of 4 cases - Souza, Glenda Brauer Bonjardim de; Nery, Caio Augusto de Souza; Prado, Marcelo Pires; Alloza, José Felipe Marion; Godoy-Santos, Alexandre Leme (Scientific Journal of the Foot & Ankle, 2019)
Osteochondral lesions of the talus are common, and the choice of treatment is based on the extent, depth and symptoms. Osteochondral autografts are indicated for large, deep and recurrent lesions. The authors describe the treatment of these lesions using an en bloc osteochondral autograft obtained from the lateral trochlea of ​​the ipsilateral knee performed in 4 ankles and evaluate the outcomes in the medium term with regard to complaints in the recipient site, donor site and aspect of the reconstructed site. The described procedure proved to be effective in the treatment of complex osteochondral lesions of the talus, restoring the normal functional pattern in the final evaluation. Level of Evidence V; Therapeutic Studies; Expert Opinion.